Review on the Epidemiology, Public Health Importance and Status of Awareness of camel rearing pastoral communities of Ethiopia on camel tuberculosis - Zelalem Ayana Dibessa (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
In the pastoral areas of Ethiopia, camel is the spine for their everyday life and extraordinarily adjusted to cruel condition. In Ethiopia, camels are for the most part raised in Afar, Somali, and Oromia (Borena, Kereyu and Guji). The pastoral community utilized camel products, such as milk and meat, and they used camels for various purposes for example, for transportation, draft, ploughing land, festivity and rivalry as in dashing. In the pastoral areas of Ethiopia, camel milk is accepted as treatment for gastritis, asthmatics, stomach inconvenience, HIV, hamot (kar), tuberculosis, fever, urinary issues and hepatitis. Camels have high contribution in Economic development of the country. In spite of having such like various purposes for pastoral areas, a few ailments influence the wellbeing status of camel. From significant illnesses, tuberculosis is one of the principal, which influence the camel Health and have a zoonotic impact.